Life lost due to the COVID-19 pandemic: A model-based cohort analysis of mortality displacement in the registered population of England - Andrew Hughes; Sharmani Barnard; Clarissa Bauer-Staeb; Richard Holleyman; Samantha Dunn; Paul Fryers; John N. Newton; Justine Fitzpatrick; Paul Burton; Peter Goldblatt (PLoS ONE, 2026)
Background Uncertainty about the prior health status of those dying during the pandemic has fuelled debate about its impact. To date, attempts to quantify life years lost during the pandemic have relied on using life tables without taking into account varying levels of vulnerability among those that died. Methods Using retrospective, linked data from March 2020 to September 2022 for the cohort of all individuals in England alive at outset, we quantified the risk of death, associated with a wide variety of comorbidities, using primary care and hospital data, as well as evidence of vaccination and COVID-19 infection. We then simulated the survival of every individual in the population with a positive COVID-19 test, with and without the assumption that COVID-19 affected their survival, taking account of their personal vulnerability. We used the difference between these simulated survival times to estimate mortality displacement (how long those who died would have lived, had they not tested positive). We used the displacement estimates for those aged 65 and older to revise estimates of excess deaths. Results We estimated median mortality displacement of 4.8 (IQR = 1.5 to 16) years for females and 4.4 (IQR = 1.4 to 12.6) years for males at ages 65 and over. We estimate 28% of those dying with COVID-19 aged 65 and over would have survived five years or more without the infection (66% for females aged 65–74). Conclusions Life expectancy of those who died with COVID-19 was substantial and, based on our analysis of vulnerability, most of those who died at ages 65 and over are unlikely to have been close to death. In future pandemics, real-time modelling of displacement would be helpful in assessing the mortality impact of the pandemic.